2023
DOI: 10.3390/nu15071574
|View full text |Cite
|
Sign up to set email alerts
|

Association between Skeletal Muscle Mass-to-Visceral Fat Ratio and Dietary and Cardiometabolic Health Risk Factors among Korean Women with Obesity

Abstract: Sarcopenic obesity (SO) is more associated with cardiovascular diseases than sarcopenia or obesity alone. This study aimed to assess the association between the skeletal muscle mass-to-visceral fat area ratio (SVR) and dietary and cardiometabolic health risk factors in obese women. Fifty-nine women aged 19–65 years with BMI values of ≥25 kg/m2 and <32 kg/m2 were included. The SVR was inversely correlated with blood lipids (total cholesterol, β = −0.369, p = 0.022; low-density lipoprotein cholesterol, β = −0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Wang et al 22 found that an increasing SVR was closely associated with an increased risk for exacerbating type 2 diabetes and metabolic syndrome. Lim et al 23 conducted a survey indicating that an elevated SVR was inversely correlated with TC and LDL‐C. In our study, participants with a lower SVR tended to have a higher prevalence of cardiometabolic risk factors.…”
Section: Discussionsupporting
confidence: 45%
“…Wang et al 22 found that an increasing SVR was closely associated with an increased risk for exacerbating type 2 diabetes and metabolic syndrome. Lim et al 23 conducted a survey indicating that an elevated SVR was inversely correlated with TC and LDL‐C. In our study, participants with a lower SVR tended to have a higher prevalence of cardiometabolic risk factors.…”
Section: Discussionsupporting
confidence: 45%
“…B6 status has frequently been studied alongside vitamin B12 and folate due to their interconnected role in one-carbon and homocysteine metabolisms. Among the seventeen studies including results for B12 [ 10 , 12 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 24 , 29 , 30 , 31 , 32 , 33 , 34 ] ( Table 1 , Table 2 and Table 3 ), four studies indicated a significant association with disability [ 14 ], skeletal muscle mass [ 17 ], all-cause mortality [ 31 ], and CVD-specific mortality [ 34 ]. Among the fourteen studies including results for folate [ 10 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 29 , 30 , 31 , 32 , 33 ], three studies indicated a significant association between the nutritional status of folate and the risks of frailty [ 18 ], heart failure [ 22 ], and all-cause mortality [ 31 ].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Regarding vitamin B2 [ 12 , 17 , 20 , 21 , 25 , 29 , 32 ] and A [ 12 , 14 , 15 , 16 , 17 , 19 ], all the studies indicated no association with sarcopenia, frailty, and mortality ( Table 1 , Table 2 and Table 3 ). Among the seven studies including results for niacin [ 12 , 17 , 20 , 25 , 29 , 31 , 32 ], only one study indicated a significant association with all-cause mortality [ 31 ]. Among the six studies including results for vitamin D [ 12 , 14 , 15 , 16 , 17 , 19 ], one study indicated a significant association with the loss of muscle [ 16 ].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 2 more Smart Citations